Utilization of biochars from wastes of thermochemical processes as adsorbents - Mahmoud, Dalia Khalid (2016)
Thermochemical conversion technologies generate large amounts of biochars as byproducts. Biochars are low value by-products that have received lesser attention and there is no valuable utilization method. On other hand, the removal of Methylene Blue (MB) dye from textile wastewater is environmentally important since MB could cause harmful effects. Kenaf core fibre char (KFC), palm oil empty fruit bunch char (EFBC) and Leucaena leucocephala wood char (LC), the by-products from gasification and pyrolysis processes at high temperature were evaluated as potential adsorbents in textile wastewater treatment in particular adsorption of MB. The adsorption of MB onto KFC, EFBC, LC and activated kenaf core fibre char (HKFC),was studied in batch process. The adsorption was performed under different operating conditions including adsorbent dose, initial dye concentration and contact time onto KFC, H-KFC, EFBC and LC of 750 μm particle size. Further conditions were studied onto H-KFC including particle size, temperature and solution pH.Adsorption isotherm and kinetics of MB adsorption onto KFC, LC, EFBC (750 μm)and H-KFC (different particle size, solution pH and temperature) were also studied.The adsorption isotherm data for all adsorbents were considered to fit well to the Langmuir model. The Langmuir adsorption capacity of MB onto adsorbents (750μm, at 30°C and solution pH=6.5) followed the trend of H-KFC>KFC>LC>EFBC.The maximum adsorption capacity of H-KFC was found increases with particle size, temperature and pH of solution (2.5- 8.5) increasing. The pseudo-second-order kinetic model described the adsorption experimental data of all adsorbents well. An analytical solution of the Langmuir kinetic model was obtained through derivation. It was found that there was a good agreement between predicted values of model and experimental data for all adsorbents. From the thermodynamic study of MB adsorption onto H-KFC(750 μm), it was found that the adsorption confirm the nature of chemisorption process, endothermic, increase the randomness of adsorbed species and more spontaneous nature at high temperature. The desorption study revealed that H-KFC(750 μm) could not be regenerated. The design of a batch adsorption study showed that H-KFC(750 μm) is more suitable to be used as adsorbent from an economical point of view. Analysis of Variance (ANOVA) results showed a significant difference between the amount of dye adsorbed at different adsorbents at all concentrations. There were no significant differences between the data at different pH and temperature at all concentrations while the effect of particle size seems obvious at the initial dye concentration of 50 mg/L. ANOVA confirmed the result of batch adsorption design where the H-KFC(750 μm) was found to be more economically suitable than the other adsorbents. A Logical study for the comparison of chemical and physical properties of adsorbents showed that the better properties trend was followed H-KFC(750 μm)>KFC(750 μm) >EFBC(750 μm)>LC(750 μm).